Therapeutic Effects of Morus alba Leaf Extract on Fasting Blood Glucose and Pancreatic β-Cell Restoration in HFD–STZ-Induced Diabetic Rats - Mirnawati Salampe; Dewa Ayu Diah Widiasri; Nurzadrina Wahyuddin; Rezki Rahayu Agus; Imrawati Imrawati; Akbar Awaluddin; Wahyuni Wahyuni (Jurnal Jamu Indonesia, 2026)
Type 2 diabetes mellitus (T2DM) is characterized by chronic hyperglycemia caused by insulin resistance and pancreatic β-cell dysfunction. Morus alba leaves contain bioactive compounds with potential antidiabetic activity. This study evaluated the hypoglycemic and β-cell protective effects of ethanolic M. alba leaf extract (EMA) in diabetic rats. The extract was obtained through maceration, yielding 12.14%. Wistar rats were divided into normal control, negative control, positive control, EMA100 (100 mg/kg BW), and EMA200 (200 mg/kg BW). Diabetes was induced using a high-fat diet, 2% sucrose solution, and low-dose streptozotocin. Fasting blood glucose (FBG) and pancreatic histopathology were analyzed. EMA significantly reduced FBG and improved pancreatic β-cell morphology, particularly at 200 mg/kg BW. These findings suggest that EMA has potential as a therapeutic candidate for T2DM by improving glycemic control and preserving pancreatic β-cell integrity.